2011
DOI: 10.5402/2011/812049
|View full text |Cite
|
Sign up to set email alerts
|

Toxins and Antibiotic Resistance in Staphylococcus aureus Isolated from a Major Hospital in Lebanon

Abstract: Molecular characterization of Staphylococcus aureus is of both clinical and infection control importance. Virulence determinants using PCR and multiple drug resistance profiles were studied in 130 S. aureus isolates. PCR-RFLP analysis of the 16S-23S DNA spacer region was done to investigate the level of 16S-23S ITS (internal transcribed spacer) polymorphism. Methicillin-resistant S. aureus (MRSA), which represented 72% of the studied isolates, showed multiple drug resistance with 18% being resistant to 10-18 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
26
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 41 publications
12
26
3
1
Order By: Relevance
“…Other studies have also reported that up to 58% of MRSA strains were tsst-1 gene positive 33,36,37 . Similar to our findings, the prevalence of tsst-1 gene was reported up to 56% among the MSSA isolates in other studies [24][25][26]38 .…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also reported that up to 58% of MRSA strains were tsst-1 gene positive 33,36,37 . Similar to our findings, the prevalence of tsst-1 gene was reported up to 56% among the MSSA isolates in other studies [24][25][26]38 .…”
Section: Discussionsupporting
confidence: 92%
“…We also found statistically signifi cant (p<0.05) association between the levels of resistances to penicillin, cefalotin, cefazoline, and ceftriaxone with mupirocin, rifampicin, trimethoprim, imipenem and gentamicin antibiotics. Tokajian et al [2] reported that 72 of S. aureus isolates of Lebanon' s hospitals were meticillin-resistant and 18 of them were resistant to 10-18 antibiotics. Study of Udo et al [4] showed that 1,765 (95.6) inpatients and 81 (4.4) outpatients of Kuwait hospitals were positive for S. aureus with 32 incidence rate of the meticillin resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Th e bacterium can colonize individuals both in the community and hospital settings [1]. Infections caused by this bacterium are treated mainly with meticillin but in recent years, increasing numbers of meticillin resistant S. aureus (MRSA) strains have been reported worldwide from patients with community-acquired infections [2][3][4]. Globally, fi fteen to forty fi ve percent of S. aureus strains isolated from hospital infections were meticillin resistant [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of MRSA in various types of clinical infections were also reported by Alghaithy et al, (2000) (61% in Saudi-Arabia) 26 , M³ynarczyk et al, (2001) (40% in Warszawie) 27 and Rijal et al, (2008) (56.1% in Pokhara) (28). Virdis et al, (2010) 29 showed that the prevalence of resistance of S. aureus against kanamycin, oxytetracycline and ampicillin were 28%, 16% and 12%, respectively. Deng et al, (2013) 30 reported that the high prevalence of resistance of the S. aureus against most commonly used antibiotics including naficillin, oxacillin, vancomycin and cefathiamidine.…”
Section: Discussionmentioning
confidence: 52%
“…It has been documented that majority of S. aureus strains were resistant to sulfamethoxazole-trimethoprim, erythromycin, oxacillin, ampicillin, penicillin, tetracycline, chloramphenicol, cotrimoxazole, gentamicin, cefexim and clindamycin 7,8 . In recent years prevalence of resistance against methicillin and vancomycine has been increased throughout the world [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%